Activable Multi-Modal Nanoprobes for Imaging Diagnosis and Therapy of Tumors - Yang, Yan; Yue, Saisai; Qiao, Yuanyuan; Zhang, Peisen; Jiang, Ni; Ning, Zhenbo; Liu, Chunyan; Hou, Yi (Frontiers in Chemistry, 2021)
Malignant tumors have become one of the major causes of human death, but there remains a lack of effective methods for tiny tumor diagnosis, metastasis warning, clinical efficacy prediction, and effective treatment. In this context, localizing tiny tumors via imaging and non-invasively extracting molecular information related to tumor proliferation, invasion, metastasis, and drug resistance from the tumor microenvironment have become the most fundamental tasks faced by cancer researchers. Tumor-associated microenvironmental physiological parameters, such as hypoxia, acidic extracellular pH, protease, reducing conditions, and so forth, have much to do with prognostic indicators for cancer progression, and impact therapeutic administrations. By combining with various novel nanoparticle-based activatable probes, molecular imaging technologies can provide a feasible approach to visualize tumor-associated microenvironment parameters noninvasively and realize accurate treatment of tumors. This review focuses on the recent achievements in the design of “smart” nanomedicine responding to the tumor microenvironment-related features and highlights state-of- the-art technology in tumor imaging diagnosis and therapy.